49PBiochemical study on modifying role of variants of leptin gene and its receptor on serum leptin levels in breast cancer. (24th November 2019) - Alhanafy, A M; Tayel, S; Ahmed, S; Altorgoman, A; Elsayed, I
Abstract: Background: Leptin is produced by adipose tissue of breast and is overexpressed in Breast cancer. Association of leptin gene (LEP) and leptin receptor gene (LEPR) polymorphisms with Breast cancer are inconsistent. Only a very few studies have examined this biochemical and genetic variables so we planned to investigate this association and its impact on leptin level and disease characteristics. Methods: Study included 70 females (40 women with pathological prove of invasive Breast cancer patients and 30 controls). Staging was done according to the American Joint Committee on Cancer 8th edition. LEP and LEPR polymorphisms were estimated by real time PCR. Serum leptin was measured by ELISA. Results: Both LEPR rs 1137101 and LEP rs 7799039 increase risk of breast cancer where GG genotype and G allele frequencies of LEPR rs 1137101 were significantly higher in patients than control [52.5% vs 16.7% and 68.8% vs 36.7%] (p = 0.002) and (p < 0.001) respectively. GG genotype increase risk of BC with [OR 9.1: 95% CI 2.30-35.94] while G allele predispose to disease with [OR 3.8: 95% CI 1.87 – 7.70]. Furthermore, LEP rs 7799039 A allele was markedly elevated in patients (61.2%) than healthy ones (43.3%) (p = 0.037) with [OR 2.06: 95% CI 1.05 – 4.08]. Leptin levels were markedly elevated than healthy ones (p < 0.001). Conclusions: Results clarified interesting relation of circulating leptin level and LEP and LEPR polymorphisms with predicting Breast cancer that may be implicated in pathogenesis of disease. Legal entity responsible for the study: Menoufia University. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.